Iatrogenic Leptomeningeal Carcinomatosis Following Craniotomy for Resection of Metastatic Serous Ovarian Carcinoma: A Systematic Literature Review and Case Report - Stopa, Brittany M.; Cuoco, Joshua A.; Adhikari, Srijan; Grider, Douglas J.; Rogers, Cara M.; Marvin, Eric A. (Frontiers in Surgery, 2022)
Metastasis of ovarian carcinoma to the central nervous system occurs in less than 2% of cases and classically localizes within the brain parenchyma. Moreover, leptomeningeal spread of these tumors is an exceedingly rare phenomenon. Here we conduct a systematic review of the current literature on the natural history, treatment options, and proposed pathogenic mechanisms of leptomeningeal carcinomatosis in ovarian carcinoma. We also report a case of a 67-year-old female with stage IV metastatic ovarian serous carcinoma initially confined to the peritoneal cavity with a stable disease burden over the course of three years. Follow-up imaging demonstrated an intracranial lesion, which was resected via craniotomy, and pathology was consistent with the original diagnosis. Three months after surgery, she developed rapidly progressive dizziness, generalized weakness, fatigue, and ataxia. Repeat MRI demonstrated interval development of extensive diffusely-enhancing dural nodularity, numerous avidly-enhancing supratentorial and infratentorial lesions, enhancement of the bilateral trigeminal nerves, internal auditory canals, and exit wound from the surgical site into the posterior aspect of the right-sided neck musculature consistent with diffuse leptomeningeal dissemination. The present case highlights that leptomeningeal dissemination of ovarian carcinoma is a potential yet rare consequence following surgical resection of an ovarian parenchymal metastasis. Progressive clinical symptomatology that develops post-operatively in this patient population should prompt urgent workup to rule out leptomeningeal disease and expedited radiation oncology consultation if identified.